Summary: Unravelling a Mystery: The Influences of Deliberative Minipublics on Public Decision-Making - Vrydagh, Julien (Politics of the Low Countries, 2025)
The PhD thesis starts with a comparative analysis of minipublics’ purposes in theory and practice. Drawing from a thematic analysis of the stated justification in the public reports of fifty-one minipublics held in Belgium between 2001 and 2021, the findings show that influencing policymaking is their most common purpose, further stressing the need to study their impact more closely. The analysis also reveals important discrepancies between theory and practice, as the latter tends to have much higher expectations. This finding suggests the formation of a minipublic bubble which inflates their actual potential to solve problems. This minipublic bubble is problematic because it is destined to burst and lead to the discredit of minipublics, as people will witness that society’s problems persist and worsen in parallel to and despite the proliferation of minipublics.